2018
DOI: 10.1002/2017jc013355
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Flood Risk Under Sea Level Rise and Extreme Sea Levels Scenarios: Application to the Ebro Delta (Spain)

Abstract: This study presents a novel methodology to estimate the impact of local sea level rise and extreme surges and waves in coastal areas under climate change scenarios. The methodology is applied to the Ebro Delta, a valuable and vulnerable low‐lying wetland located in the northwestern Mediterranean Sea. Projections of local sea level accounting for all contributions to mean sea level changes, including thermal expansion, dynamic changes, fresh water addition and glacial isostatic adjustment, have been obtained fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 63 publications
3
30
0
Order By: Relevance
“…Therefore, to take the most appropriate mitigation and adaptation measures, it is necessary to perform local studies accounting for all physical variables to determine the impact of SLR over the coastal zones. Sayol and Marcos (2018), estimated the impact of local sea level rise, extreme surge and waves in the Ebro Delta (Spain) under the climate change scenarios RCP4.5 and RCP8.5. The results show that for the year 2050 under the RCP 4.5 and RCP 8.5 sea level rise will flood a 65% of the Delta in both cases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, to take the most appropriate mitigation and adaptation measures, it is necessary to perform local studies accounting for all physical variables to determine the impact of SLR over the coastal zones. Sayol and Marcos (2018), estimated the impact of local sea level rise, extreme surge and waves in the Ebro Delta (Spain) under the climate change scenarios RCP4.5 and RCP8.5. The results show that for the year 2050 under the RCP 4.5 and RCP 8.5 sea level rise will flood a 65% of the Delta in both cases.…”
Section: Discussionmentioning
confidence: 99%
“…Then, correlation is assessed with the Kendall rank correlation. Previous studies in the US coast and globally have suggested that an indicative value of 0.2 may be already significant enough (Wahl and Chambers, 2014) to require the computation of the joint probability using a multivariate approach such as the Copula functions (e.g., Sayol and Marcos, 2018;Enríquez et al, 2019;Marcos et al, 2019). Correlations for those independent events are shown in Figure 4C for all percentiles being in all cases very low with FIGURE 5 | Schematic representation of the approach followed in the study.…”
Section: Correlation Between Skew-surges and H Smentioning
confidence: 99%
See 1 more Smart Citation
“…Here we have selected the most probable pair of surge‐ H s . This approach was also applied in Sayol and Marcos () for a local case study.…”
Section: Methodsmentioning
confidence: 99%
“…Given the threats that climate change and the associated SLR pose to the coastal regions, the assessments of future coastal vulnerability have become topic research issues in the last years (Nicholls, 2002;Revell et al, 2011;Idier et al, 2013;Le Cozannet et al, 2014;Ranasinghe, 2016;Luijendijk et al, 2018;Sayol and Marcos, 2018) as well as their socio-economic consequences (Small and Nicholls, 2003;Dasgupta et al, 2009;Gössling et al, 2012). Among these, studies focused on sandy shores, mostly beaches, are very common because this type of coasts is subject to a very high level of human utilization (Gössling et al, 2012).…”
Section: Introductionmentioning
confidence: 99%